EFFECTIVENESS OF GUIDED INQUIRY BASED WORKSHEET TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS ON THE MATERIAL OF VIRUS REPLICATION - Permatasari, Anggi; Tri Asri, Mahanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of guided inquiry based worksheet on virus replication material to improve critical thinking skills of grade X high school students. The study used the method Research and Development (R&D) with a 4D development model (Define, Design, Develop, And Disseminate). A limited trial was conducted on 30 grade X high school students. The research instrument used was a critical thinking skills test based on Facione (2015) indicators, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data were analyzed using percentages and N-gain. The results showed that worksheet effectively improved critical thinking skills with an average pre-test score of 80.83 and a post-test score of 96.95, as well as an average N-gain of 0.84, categorized as high. Thus, the guided inquiry based student worksheet on virus replication was declared effective in improving students' critical thinking skills.